Strategic Planning of Prospects to Develop Management Models in Digital Economy - N. S. Mrochkovsky (Вестник Российского экономического университета имени Г. В. Плеханова, 2020)
The article shows initiative in the field of state support for progressive development and upgrading systems of managing entities of small and medium intellectual business in national economy. It includes setting-up a special federal foundation to support initiatives in the sphere of information market, providing broadest opportunities for using federal and regional innovation infrastructure, stimulating commercial banks of the Russian Federation to intensify crediting of entities of small and medium information business in Russia and tax preferences. The author highlights steps aimed at the development of strategic management of small and medium information entities’ work as residents of Russian Federation economy. This covers improvement of cloud technology use, development of integration processes in the field of managing entities of small and medium information business in Russia, growth in the efficiency of managing information security and enhancement of economic potential use of social networks in organization governance. The author puts forward a model of mega-integrator of digital platform management as a unique information and communication space, which provides opportunities for organizations to choose the most preferable managerial variants of using the broadest range of digital platforms.